A neurobiological association of revenge propensity during intergroup conflict - Xiaochun Han; Michele J Gelfand; Bing Wu; Ting Zhang; Wenxin Li; Tianyu Gao; Chenyu Pang; Taoyu Wu; Yuqing Zhou; Shuai Zhou; Xinhuai Wu; Shihui Han (eLife, 2020)
Revenge during intergroup conflict is a human universal, but its neurobiological underpinnings remain unclear. We address this by integrating functional MRI and measurements of endogenous oxytocin in participants who view an ingroup and an outgroup member's suffering that is caused mutually (Revenge group) or by a computer (Control group). We show that intergroup conflict encountered by the Revenge group is associated with an increased level of oxytocin in saliva compared to that in the Control group. Furthermore, the medial prefrontal activity in response to ingroup pain in the Revenge group but not in the Control group mediates the association between endogenous oxytocin and the propensity to give painful electric shocks to outgroup members, regardless of whether they were directly involved in the conflict. Our findings highlight an important neurobiological correlate of revenge propensity, which may be implicated in conflict contagion across individuals in the context of intergroup conflict.